Characteristics and reactivity of La-Co-Cu based perovskites for the liquid oxidation of styrene - Thao, Nguyen Tien; Tuan, Nguyen Anh (Vietnam Journal of Chemistry, 2014)
LaCo1-xCuxO3 (0.0 ≤ x ≤ 0.3) samples prepared by the conventional citrate method show a well perovskite structure although the solid products still have a small amount of constituent oxides. The mixed oxide powder possesses slit-like pores formed from the voids between by spherical nanoperovskite particles. An insertion of copper into La-Co perovskite lattice makes an observable decrease in perovskite particle size. All the synthesized perovskites were used as catalysts for the liquid oxidation of styrene. Under typically experimental conditions, styrene reagent was firmly converted into the benzaldehyde product over the synthesized perovskite catalysts at the moderate conversion in the range of 1-5 %. Keywords: La-Co-Cu-O, Perovskite, nanoperovskite, styrene, oxidation.